NEUROPROTECTIVE PROPERTIES OF NEUROPEPTIDES - Kanunnikova N. P. (Žurnal Grodnenskogo Gosudarstvennogo Medicinskogo Universiteta, 2017)
The main mechanisms of action of neuropeptides are regulation of energy metabolism and redox-balance of brain tissue, neurotrophic effects and modulation of activity of endogenous growth factors, interaction with systems of neuropeptides and neurotransmitters. The main spectrum of their pharmacological activity is neuroprotection during various types of neurodegeneration, increasing the ability to learn and memorize, increasing the stress-resistance of the organism. Neuropeptides are highly effective in the intranasal route of administration. The review considers the neuroprotective properties of Semax, insulin-like growth factor-1, cortexin, deltaran, cerebrolysin, dipeptides of leucyl-isoleucine and glycyl-proline.